PVA stabilized gold nanoparticles by use of unexplored albeit conventional reducing agent - Khanna, P. K.; Gokhale, R.; Subbarao, V. V. V. S.; Vishwanath, A. K.; Das, B. K.; Satyanarayana, C. V. V. (Materials Chemistry and Physics, 2005)
Poly(vinyl alcohol) (PVA) stabilized gold nanoparticles have been prepared in aqueous medium using two different reducing viz.; hydrazine hydrate, a stronger reducing agent and sodium formaldehydesulfoxylate (SFS), a slightly weaker reducing agent. SFS is used for first ever time for reduction of gold metal salt. The PVA stabilized gold nanoparticles solutions are wine red to blood red coloured and are stable over a long period of time with no indication of aggregation. The solution shows strong visible light absorptions in the range of 520-540 nm, characteristics of gold nanoparticles. Powder X-ray diffraction patterns of freshly prepared films containing gold nanoparticles indicated particles size to be about 15 nm. Transmission electron microscopy (TEM) of a more than two-week-old sample revealed well-defined non-agglomerated spherical particles of about 50 nm diameter in solutions. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; electronic materials; Nanostructures; Polymer

Nature and mode of addition of phosphate precursor in the synthesis of aluminum phosphate and its influence on methanol dehydration to dimethyl ether - Kumar, V. Siva; Padmasri, A. H.; Satyanarayana, C. V. V.; Reddy, I. Ajit Kumar; Raju, B. David; Rao, K. S. Rama (Catalysis Communications, 2006)
Four aluminum phosphate catalysts with Al/P = 1 were prepared by precipitation of mixture of aluminum nitrate and phosphate precursor (either phosphoric acid or diammonium hydrogen phosphate) with NH3 and precipitation of aluminum nitrate with NH3 followed by impregnation of phosphate precursor (either phosphoric acid or diammonium hydrogen phosphate). The catalysts were characterized, using different physico-chemical methods viz., BET-S.A., XRD, FT-IR, and NH3-TPD. Al-27 and P-31 MAS NMR spectroscopy was used to characterize selected catalysts in order to find out the presence of Al and P environments. The catalytic conversion of methanol to dimethyl ether was conducted over these catalysts in a temperature range of 448-548 K at atmospheric pressure. AIPO(4) prepared by precipitating the mixture of aluminum nitrate and (NH4)(2)HPO4 with aq. NH3 generated more number of moderate acid sites and showed higher methanol dehydration activity with 100% selectivity to DME at 548 K. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Al-27 and P-31 MAS NMR; aluminum phosphate; dehydration; dimethyl ether; Methanol; NH3-TPD

Incorporation of zirconium in medium-pore aluminophosphate molecular sieves with AEL framework - Ganguli, J. N.; Chakrabortty, Dhruba; Satyanarayana, C. V. V. (Microporous and Mesoporous Materials, 2008)
Zirconium incorporated alurninophosphate molecular sieves ZrAPO-11 was synthesized by hydrothermal method. The samples were characterized by X-ray diffraction (XRD), scanning electron microscopy, thermogravimetric/differential thermal analysis (TGA/DTA), diffuse reflectance UV-visible spectroscopy, magic-angle spinning nuclear magnetic resonance (MAS NMR) spectroscopy (P-31 and Al-27). The acidity of the materials were determined by temperature programmed desorption (TPD) of ammonia. X-ray diffraction and scanning electron microscopy reveals formation of crystalline material in pure phase. Thermal analysis shows higher template content in zirconium containing samples than the corresponding AlPOs. MAS NMR suggests incorporation of zirconium in the framework. TPD reveals that the ZrAPO-11 samples were of higher acidity than AIPO(4)-11 (c) 2007 Elsevier Inc. All rights reserved.
Keywords: AlPO4-11; Aluminophosphate; catalysis; Molecular sieve; ZrAPO-11

Synthesis of oleic acid capped copper nano-particles via reduction of copper salt by SFS - Khanna, P. K.; Kale, Trupti S.; Shaikh, Mushtaq; Rao, N. Koteswar; Satyanarayana, C. V. V. (Materials Chemistry and Physics, 2008)
Synthesis of oleic acid capped copper nano-particles has been carried out by use of sodium formaldehyde sulfoxylate (SFS) in aqueous medium. Nano-copper can be effectively coated with polyvinyl alcohol (PVA). Phase-pure nano-Cu can be obtained when water/acetone was used as aqueous medium. It is observed that the surface plasmon resonance (SPR) phenomena can be controlled during synthesis by the use of suitable reagent system, e.g. absorption band in presence of PVA can be blue shifted. As-prepared copper nano-particles were characterized by X-ray diffraction measurements (XRD), Scanning electron microscopy (SEM), energy dispersive analysis of X-rays (EDAX), thermo gravimetric analysis (TGA) and Fourier transform infra-red spectroscopy (FTIR). XRD analysis revealed broad pattern for fcc crystal structure of copper metal. The particle size by use of Scherrer's equation was calculated to be about 20 nm. TGA revealed similar to 10% weight loss due to the presence of surfactant. FTIR spectroscopy confirmed the presence of oleic acid around the particles. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; electronic materials; metals; Nanostructure

Incorporation of zirconium in medium-pore aluminophosphate molecular sieves with AFO framework - Chakrabortty, Dhruba; Ganguli, J. N.; Satyanarayana, C. V. V. (Microporous and Mesoporous Materials, 2011)
Zirconium substituted medium pore microporous aluminophosphate molecular sieve ZrAPO-41 was prepared by hydrothermal synthesis under autogenous pressure The formation of the pure phase was confirmed by powder X-ray diffraction (XRD) and scanning electron microscopy (SEM)The thermal behaviour of the material was investigated by carrying out thermogravimetric/differential thermal analysis (TGA/DTA) The zirconium environment was studied by magic-angle spinning nuclear magnetic resonance (MAS NMR) spectroscopy which suggests incorporation of zirconium into the framework UV-Visible diffuse reflectance study also supports the claim The temperature programmed desorption (TPD) of ammonia reveals that the acidity of ZrAPO 41 samples is higher than that of pure AlPO4-41 The catalytic activity of the samples was investigated through phenol hydroxylation reaction The result show hi E her catalytic activity for ZrAPO-41 samples compared to AlPO4-41 (C) 2010 Elsevier Inc All rights reserved
Keywords: AFO; Aluminophosphate; catalysis; Molecular sieve; ZrAPO 41

Oxidative dehydrogenation of ethylbenzene using nitrous oxide over vanadia-magnesia catalysts - Shiju, N. Raveendran; Anilkumar, Mettu; Gokhale, S. P.; Rao, B. Seshagiri; Satyanarayana, C. V. V. (Catalysis Science & Technology, 2011)
A series of V-Mg-O catalysts with different loadings of vanadia were prepared by the wet impregnation method and the effect of the local structure of these catalysts on the oxidative dehydrogenation of ethylbenzene with N(2)O was investigated. High styrene selectivity (similar to 97%) was obtained at 773 K. The characterization of catalysts with methods such as XRD, FTIR, UV-visible, TPR, NMR and Laser Raman spectroscopy suggested that magnesium orthovanadate is the predominant vanadium containing phase and the size of the orthovanadate domains increases with increasing vanadia loading. The rate of ODH of ethylbenzene per V atom increases with vanadia loading and reaches a maximum at 10 wt%. The specific activity, i.e. the conversion of ethylbenzene per unit surface area of the catalysts, also exhibited a maximum at a vanadia loading of 10 wt% leading to the conclusion that activity of these catalysts is due to the presence of very small domains of Mg(3)(VO(4))(2) on the surface of MgO rather than crystallites of bulk Mg(3)(VO(4))(2). The higher styrene yield in the presence of N(2)O can be ascribed to the ability of N(2)O to keep vanadium species at a higher oxidation state.

Preferential oxidation of CO on Ni/CeO2 catalysts in the presence of excess H-2 and CO2 - Malwadkar, Sachin S.; Bera, Parthasarathi; Hegde, M. S.; Satyanarayana, C. V. V. (Reaction Kinetics Mechanisms and Catalysis, 2012)
Preferential oxidation of CO (CO-PROX) was carried out over Ni supported on CeO2 prepared by the co-precipitation method. The influence of metal loadings (2.5, 5 and 10 wt.% Ni) and the reaction conditions such as reaction temperature and feed composition on CO oxidation and oxidation selectivity were evaluated by using dry reformate gas. No other reactions like CO or CO2 methanation, coking, reverse water gas shift (RWGS) reaction is observed in the temperature range of 100-200 A degrees C on these catalysts. Hydrogen oxidation dominates over CO oxidation above the temperature of 200 A degrees C. An increase in oxygen leads to an increase in CO conversion but a simultaneous decrease in the O-2 selectivity. It has been noticed that 5 and 10 % Ni/CeO2 show better catalytic activity towards CO-PROX reaction. These catalysts were characterized by S-BET, XRD, TEM, XPS and H-2-TPR.
Keywords: CeO2; CO-PROX; fuel cells; Methanation; Ni

Influence of method of preparation on the activity of La-Ni-Ce mixed oxide catalysts for dry reforming of methane - Sagar, T. V.; Sreelatha, N.; Hanmant, G.; Surendar, M.; Lingaiah, N.; Rao, K. S. Rama; Satyanarayana, C. V. V.; Reddy, I. A. K.; Prasad, P. S. Sai (RSC Advances, 2014)
La-Ni-x-Ce1-x mixed oxide catalysts were prepared by a sol-gel method varying the Ni composition (0 <= x <= 1). The catalysts were characterized by X-ray diffraction (XRD), inductively coupled plasma optical emission spectroscopy (ICP-OES), BET surface area, X-ray photoelectron spectroscopy (XPS), temperature-programmed reduction (TPR), H-2 chemisorption and Fourier transform infrared spectroscopy (FT-IR) techniques. CO2 reforming of methane was carried out at atmospheric pressure and 800 degrees C, maintaining a reactant CO2/CH4/N-2 ratio of 80/80/80 (total flow rate = 240 ml min(-1), GHSV of 28 800 h(-1)). The catalysts offered higher activity even at lower Ni compositions. LaNi0.4Ce0.6O3. showed the highest conversion of CH4 and CO2. The H-2/CO ratio in the syngas was stable at 0.85 +/- 0.02. The performance of the sol-gel catalysts was compared with that of the hydrothermally prepared catalysts, reported earlier. High surface area and better Ni dispersion were found to be the reasons for superior activity of the sol-gel catalysts.

Methane reforming with carbon dioxide over La-Ni-x-Ce1-x mixed oxide catalysts - Sagar, T. V.; Sreelatha, N.; Hanmant, G.; Upendar, K.; Lingaiah, N.; Rao, Kamaraju Seetha Rama; Satyanarayana, C. V. V.; Reddy, I. A. K.; Prasad, P. S. Sai (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2014)
La-Ni-x-Ce1-x mixed oxide (0 <= x <= 1) catalysts have been hydrothermally prepared, characterized by physico-chemical techniques and evaluated for CO2 reforming of methane. High conversions are achieved for both methane and carbon dioxide over the LaNi0.6Ce0.4O3 catalyst tested under the conditions of CO2/CH4/N-2 ratio of 80/80/80. (total flow rate = 240 mL/min), space velocity of 28,800 h(-1) and at a temperature of 800 degrees C. The H-2/CO ratio in the syngas is stable at 0.93 +/- 0.02. Exchanging Ni with Ce, rather than with La as reported in the literature, appears to be a better option for the improved performance of the catalysts.
Keywords: Carbon dioxide reforming; Catalysts; Cerium; Dry reforming; Hydrothermal synthesis; Lanthanum; Methane reforming; Mixed oxides; Nickel

Controlling and stabilization of Ru nanoparticles by tuning the nitrogen content of the support for enhanced H-2 production through aqueous-phase reforming of glycerol - Gogoi, Pranjal; Kanna, Narsimharao; Begum, Pakiza; Deka, Ramesh C.; Satyanarayana, C. V. V.; Raja, Thirumalaiswamy (ACS Catalysis, 2020)
The stable activity of catalysts is an important issue in catalysis, particularly aqueous-phase reforming (APR) of renewable oxygenates, of biomass origin, to get H-2. Sintering of metal nanoparticles on supports affects catalyst stability. To alleviate this problem, a series of highly stable Ru-supported catalysts with controlled metal nanoparticle sizes have been prepared via the easy incipient wetness impregnation method. These catalysts were used for APR of glycerol to produce H-2. Nitrogen-doped mesoporous carbons (NMCs) were utlized as supports and found to have a strong influence on the catalytic performance of the catalysts. Incorporation of nitrogen in the carbon framework significantly enhanced the catalytic activity compared to Ru catalysts on nitrogen-free supports. Notably, the catalyst (5 wt % Ru-NMC-3) with optimal N content (10.9 wt %) demonstrated improved stability and H-2 selectivity, which are better than those of many state-of-the-art catalysts. Nitrogen in the carbon framework has a dual relationship with the activity of the catalyst: (i) it creates basic environment over the catalysts support and (ii) it acts as an anchoring site for metal nanoparticles. Anchoring of metal nanoparticles has helped to curb their sintering, thus leading to better stability of the catalysts under APR reaction conditions. Various characterization techniques were employed to understand the nature of active catalytic sites responsible for higher H-2 production while minimizing CO formation. In situ CO-FTIR studies showed that the higher catalytic activity of 5 wt % Ru-NMC-3 catalyst was attributed to the enhanced WGS activity over this catalyst. Density functional theory calculations were performed to understand the stabilization of metal nanoparticles by different types of N present on the support and provide insights into the prefered sites of glycerol adsorption on the NMC support. Since S wt % Ru-NMC-3 was the relatively best catalyst, it was selected for the preparation of bimetallic catalysts. Accordingly, addition of Pt to this system helped to increase the stability of the catalyst. This bimetallic catalyst may, therefore, find application for wide use in APR of biomass oxygenates.
Keywords: aqueous-phase reforming; Glycerol; H-2 production; Ru/NMC catalyst; synergistic effect

Influence of cobalt on performance of Cu-CeO2 catalysts for preferential oxidation of CO - Malwadkar, Sachin; Bera, Parthasarathi; Satyanarayana, C. V. V. (Journal of Rare Earths, 2020)
{Copper and cobalt oxides supported on CeO2 were investigated for preferential oxidation of carbon monoxide (CO-PROX) in the presence of excess hydrogen and CO2. (CuO)(1-x)(Co3O4)(x/3)-(CeO2)(2.5) (x = 0, 0.25, 0.50, 0.75, 0.85 and 1) catalysts were prepared by coprecipitation method. These mixed oxide catalysts were characterized by several physicochemical techniques, such as BET surface area (SBET), X-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM), temperature programmed reduction (TPR) and X-ray photoelectron spectroscopy (XPS). XRD studies show the peaks related to CuO and Co3O4 phases in copper and cobalt containing CeO2 catalysts. The average particle size of the CeO2 crystallites is in the range of 8-10 nm as evaluated from HRTEM studies. XPS studies demonstrate that Cu, Co and Ce in (CuO)(1-x)(Co3O4)(x/3)-(CeO2)(2.5) catalysts are presented in +2 and +1, +3 and +2 and +4 and +3 oxidation states, respectively. The catalyst with x = 0.75 shows better activity and selectivity towards CO-PROX. Though the catalyst with only copper (CuO-CeO2
Keywords: CO-PROX; Cu-CeO2; H2O addition; Methanation; XPS; XRD

Insights into the catalytic activity of Ru/NaY catalysts for efficient H-2 production through aqueous phase reforming - Gogoi, Pranjal; Nagpure, Atul S.; Kandasamy, Prabu; Satyanarayana, C. V. V.; Raja, Thirumalaiswamy (Sustainable Energy & Fuels, 2020)
Ruthenium nanoparticles supported on NaY zeolite catalysts were synthesized by a simple ion exchange method. The structural and morphological features of the catalysts were systematically investigated using numerous techniques such as N-2-sorption, XRD, CO2-TPD, H-2-TPR, TEM, SEM, ICP-OES, TGA, CHN analysis, XPS, in situ CO-FTIR and NMR spectroscopy. These novel Ru-NaY catalysts were highly active and selective for H-2 production through aqueous phase reforming (APR) of glycerol and ethylene glycol. Among the various catalysts evaluated for H-2 production, the 3 wt% Ru-NaY catalyst demonstrated the highest catalytic performance with excellent H-2 selectivity and this catalyst exhibits better activity as compared to many state of the art catalysts reported so far. The superior catalytic activity of 3 wt% Ru-NaY was attributed to the appropriate Ru metal loading, good metal dispersion, small size of Ru nanoparticles, better metal-support interaction, and higher availability of catalytically active sites (Ru-0) and facilitated water gas shift (WGS) reaction. This catalytic activity result clearly shows that NaY zeolite supported Ru nanoparticles catalysts have excellent potential for H-2 production from biomass-derived compounds.